2015
DOI: 10.1021/acs.orglett.5b00936
|View full text |Cite
|
Sign up to set email alerts
|

New Method for the Rapid Extraction of Natural Products: Efficient Isolation of Shikimic Acid from Star Anise

Abstract: A new, practical, rapid, and high-yielding process for the pressurized hot water extraction (PHWE) of multigram quantities of shikimic acid from star anise (Illicium verum) using an unmodified household espresso machine has been developed. This operationally simple and inexpensive method enables the efficient and straightforward isolation of shikimic acid and the facile preparation of a range of its synthetic derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Cells were then washed at least three times using phosphate-buffered saline and treated with FITC-phalloidin for 1 h, followed by 4',6-diamidino-2-phenylindole staining for 10 min. The pit formation assay was performed as previously described [7].…”
Section: F-actin Ring Formation and Pit Formation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were then washed at least three times using phosphate-buffered saline and treated with FITC-phalloidin for 1 h, followed by 4',6-diamidino-2-phenylindole staining for 10 min. The pit formation assay was performed as previously described [7].…”
Section: F-actin Ring Formation and Pit Formation Assaysmentioning
confidence: 99%
“…Finally, intracellular Ca 2+ is released, and NFATc1 is activated and osteoclastogenesis is promoted [5]. Previous studies demonstrated that overactive osteoclast function could also be induced by a deficiency of estrogen accompanied by increased levels of proinflammatory cytokines and RANKL after menopause [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Active ingredients were extracted from BM (Chinese variety; sourced from local vegetable super market in Hobart, Tasmania, Australia labelled as bitter melon) by pressurised hot water using a modification of a method previously described for natural product isolation [27, 28]. …”
Section: Methodsmentioning
confidence: 99%
“…[17] In 2015, a pilot study demonstrated that an unmodified conventional espresso machine could be repurposed to facilitate efficient natural products extraction and, by doing so, better enable isolation studies (vide infra). [18] Minimal sample preparation is required for this particular method of PHWE. Plant material is dried and ground prior to extraction to reduce particle size, aid packing and assist the penetration of extraction solvent into the sample matrix.…”
Section: Accelerated Solvent Extraction (Ase)mentioning
confidence: 99%